Calcium/calmodulin-mediated microbial symbiotic interactions in plants - Yuan, Peiguo; Luo, Feixiong; Gleason, Cynthia; Poovaiah, B. W. (Frontiers in Plant Science, 2022)
Cytoplasmic calcium (Ca2+) transients and nuclear Ca2+ oscillations act as hubs during root nodulation and arbuscular mycorrhizal symbioses. Plants perceive bacterial Nod factors or fungal signals to induce the Ca2+ oscillation in the nucleus of root hair cells, and subsequently activate calmodulin (CaM) and Ca2+/CaM-dependent protein kinase (CCaMK). Ca2+ and CaM-bound CCaMK phosphorylate transcription factors then initiate down-stream signaling events. In addition, distinct Ca2+ signatures are activated at different symbiotic stages: microbial colonization and infection; nodule formation; and mycorrhizal development. Ca2+ acts as a key signal that regulates a complex interplay of downstream responses in many biological processes. This short review focuses on advances in Ca2+ signaling-regulated symbiotic events. It is meant to be an introduction to readers in and outside the field of bacterial and fungal symbioses. We summarize the molecular mechanisms underlying Ca2+/CaM-mediated signaling in fine-tuning both local and systemic symbiotic events.